ANALISIS OPTIMASI PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE JUST IN TIME PADA UD. KARIA JAYA - I Made Weda Adnyana; I Made Sukadana (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study is to analyze how to optimize raw material inventory using the just in time method at UD Karia Jaya. The subjects in this study were the owners and employees of the production department who worked at UD Karia Jaya. This research was conducted using qualitative research methods. Based on the results of the study showing that through interviews with related sources, it can be concluded that the existing problems are: 1. Company a. Lack of policy, b. Uncertainty, c. The turnover of money is less clear, d. Cash is not helped, e. Insecurity of transactions. as for the efforts made to facing problems that exist in the company by improving the operational management system in the company from the aspects of the company and employees, namely: 1. Company, a. Fixing the policy, b. Seeking certainty The turnover of money is less clear, c. Cash is not helped, d. Transaction insecurity and 2. Employees, 1.Strive for smooth performance and freedom from uncertainty.